Prevalence and risk factors of actinic keratoses in Germany – analysis of multisource data. (24th January 2013) - Schaefer, I.; Augustin, M.; Spehr, C.; Reusch, M.; Kornek, T.
Abstract Background In Europe, only few and inconsistent data on the prevalence and treatment of actinic keratoses (AK) are available. Objectives To determine the prevalence of AK in Germany, to identify potential predictors and to estimate the number of AK cases treated in dermatological practices. Methods In a multiple‐source approach, prevalence was assessed from whole‐body examinations in a cohort of 90 800 employees and from nationwide statutory health insurance (SHI) data of 2008. The number of cases documented in dermatological offices was estimated from statistics of a SHI Physicians Association. Results Standardized prevalence of AK from dermatological examinations was 2.7%; the rate increased with age (11.5% in the group 60–70 years) and was higher for men (3.9%) than for women (1.5%). Significant associations were also identified for skin phototype I, sunburns in childhood and solar lentigines. Vitiligo and a history of melanoma were also, but not significantly, associated with AK. In the SHI data analysis, standardized AK prevalence was 1.8%. Age‐specific rates were below 1.5% up to 60 years and rose to 8.2% (13.2% in men) in the group 80–89 years. The prevalence from these large data sets – which is at the lower limit of studies from other countries – suggests about 1.7 million estimated AK cases in Germany. In 2011, AK accounted for 8.3% of the hundred most frequently treated dermatological outpatient diagnoses. The proportion of AK cases has risen almost continuously over the last 10 years, compared to other dermatological conditions. Estimated annual number of AK cases documented by dermatologists in Germany is about 1.7 million. Conclusions Actinic keratosis is a frequent condition in higher age groups and more prevalent in men; a relevant need for health care is evident. Predictors and risk factors for AK are easy to identify in the population, which could also help to detect groups with special need for preventive measures.